S164 Diminished left ventricular end-diastolic dimensions predict an amplified risk of death in chronic obstructive pulmonary disease. (16th November 2010) - Mendonca, M; Brown, J; Rashid, M; Ling, H Z; Kang, S; Cheng, A; Boston-griffiths, E; Okorie, M; Thomas, M; Woldman, S; Booth, H; Do okonko,
Abstract : Background: Left ventricular (LV) dimensions are markedly attenuated in chronic obstructive pulmonary disease (COPD) possibly due to impairments in LV filling that result from increased pulmonary vascular resistance, ventricular interdependence, diastolic dysfunction or incessant tachycardia. Whether reductions in LV size carry adverse prognostic implications in this cohort is unclear. Methods: We analysed the relation between echocardiographic indices and mortality in 147 COPD patients (mean [±SD] age 76±10 years, forced expiratory volume in 1 s [FEV1] 0.85±0.34 l, forced vital capacity [FVC] 1.44±0.60 l, FEV1/FVC 0.62±0.16, LV ejection fraction [LVEF] 56±12%) with homogenous right ventricular (42±14 mm Hg) and pulmonary arterial systolic (45±17 mm Hg) pressures. Results: Decreased LV end-diastolic (LVEDD ≤37 mm) and end-systolic (LVESD ≤25 mm) diameters, ejection fraction (<45%), and diastolic function (E/A ratio <1 or >2) were evident in 10%, 14%, 18% and 71% of patients, respectively. Lower LVEDDs correlated significantly to lower LVESDs (r=0.83), higher LVEFs (r=−0.54), lower FEV1s (r=0.29), and lower FVCs (r=0.20) but not to age, right ventricular systolic pressures or pulmonary arterial pressures. Over a mean follow-up of 26±18 months, 60 (41%) patients died. Only a lower LVEDD predicted increased mortality (c 2 4.4, p=0.03) with each 1 mm decrement in LVEDD conferring a 3% escalated risk of death. An LVEDD ≤43 mm optimally predicted mortality and was associated with an 89% reduction in survival compared to an LVEDD >43 mm (Abstract S164 Figure 1 ). No variable affected the prognostic impact of LVEDDs in adjusted analyses. Conclusions: Attenuations in left ventricular end-diastolic diameter forecast an enhanced risk of death in patients with COPD, irrespective of lung function and pulmonary arterial pressures. Improving LV filing and dimensions in this cohort may augment survival.